Use of Oral Misoprostol, Intramuscular Oxytocin and Intravenous Methergin in Prevention of Postpartum Haemorrhage - Meena, Banwari Lal (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: The purpose of the study was to compare the efficacy of misoporstol 600mg orally (Group A), injection oxytocin 10 IU intramuscularly (Group B) and injection methylergometrine 0.2 mg intravenously (Group C) on reducing blood loss in third stage of labour, duration of third stage of labour, effect on haemoglobin of the patient, need of additional oxytocics or blood transfusion and associated side effects and complications. Methods: A prospective study enrolling 510 women and randomising them into three groups was done in S P Medical College, Bikaner, Rajasthan, India. Active management of third stage of labour was done using one of the three uterotonics as per the group of the patient. Results: Methylergometrine was superior to rest of the drugs with lowest duration of third stage of labour (p = 0.02), lowest amount of blood loss (p = 0.0001) and lowest rate of post partum hemorrhage (p = 0.08). The need of additional oxytocics and blood transfusion was highest with oral misoprostol as compared to all other drugs used in the study with p value of 0.08 and 0.009 respectively. Conclusions: Methylergometrine has the best uterotonic drug profile amongst the drugs used, strongly favouring its routine use as oxytocic for active management of third stage of labour. Oral misoprostol resulted in a higher blood loss compared to other drugs and hence it should be used only in low-resource settings where other drugs are not available. However, a large multi-centre study is needed for the confirmation of the finding. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 34-36 DOI: http://dx.doi.org/10.3126/njog.v8i1.8859